Respuesta :
Answer:
[tex]\approx 13^\circ[/tex]
Step-by-step explanation:
Given two lines with the equations:
[tex]9x - y = 4\\ 8x + y = 6[/tex]
First of all, let us learn the formula for finding the angle between the two lines with given equations:
[tex]tan\theta = \dfrac{m_1-m_2}{1+m_1m_2}[/tex]
[tex]m_1, m_2[/tex] are the slopes of the two lines respectively.
Let us convert the given equation to point intercept form.
Point intercept form of a line is given as:
[tex]y = mx+c[/tex]
[tex]y = 9x-4\\y =-8x+6[/tex]
Comparing with slope intercept form, we get:
[tex]m_1 = 9\\m_2 = -8[/tex]
Using the above formula:
[tex]tan\theta =\dfrac{9 -(-8)}{1+9(-8)}\\\Rightarrow tan\theta = -\dfrac{17}{71}\\\Rightarrow \theta = -13.46^\circ\\[/tex]
Therefore, the acute angle between the two lines is [tex]\approx 13^\circ[/tex]
The acute angles between the equations is 13.46 degree.
To find the acute angles between the two equation, let's write out the individual slope of each equation.
Given Data
- 9x - y = 4
- 8x + y = 6
Equation of line
The given equations can be rearranged into equation of line.
[tex]9x-y=4\\ y=9x-4\\ slope=m_1=9[/tex]
The second equation can also be rearranged as and solving for the slope
[tex]8x+y=6\\ y=6-8x\\ y=-8x+6\\ slope = m_2 = -8[/tex]
Since we have the slopes of the two equation, we can now find the acute angle between them.
θ = [tex]tan^-^1[\frac{m_1-m_2}{1+m_1m_2}]\\ [/tex]
substituting the values and solving for the angle
[tex]x = tan^-^1[\frac{9-(-8)}{1+(9*-8)}]\\ x = tan^-^1[17/-71]\\ x=-13.46 = 13.46^0[/tex]
The acute angle between the equations is 13.46 degree
Learn more about acute angle in equations here;
https://brainly.com/question/6979153